Exploring Dialectical Tensions of Leading Volunteers in Two Community Choirs. Issue 2 (15th March 2017) - Piercy, Cameron W.; Kramer, Michael W.
Abstract : Leaders of volunteers face different challenges than leaders of paid employees due to different motivations and reward expectations. After synthesizing previous research applying dialectical theory to group members or leaders, this study examines the dialectical tensions that leaders of volunteers experienced and the communication they used to manage those tensions as reported by both the leaders and the volunteers. A constant-comparison method was used to analyze observations and interviews of members and leaders of two community choirs. The findings suggest that leaders of volunteers face eight dialectical tensions representing three broad categories: (a) task and relationship; (b) process and outcome; and (c) internal and external. Leaders negotiated these dialectical tensions through communication strategies including use of humor and appeals to artistic spirituality. These strategies represent hybridization and dualistic discourse rather than a monologic emphasis of one course of action over another.